Effects of TiAl Alloy as a Binder on Cubic Boron Nitride Composites - Yuxi Liu (MDPI AG, 2021)
Owing to their extreme hardness, cubic boron nitride (cBN) composites are widely used in cutting applications. The performance of cBN composites is closely related to the characteristics of the binder. Therefore, novel binders must be developed to improve the performance of cBN composites. In the present work, TiAl intermetallics were used as binders to fabricate cBN composites by employing a high-temperature and high-pressure sintering method. The phase transformation, sintering reaction mechanism, thermal stability, and mechanical properties of the resultant cBN composites were investigated. It was found that during the sintering process, Ti atoms preferentially reacted with boron nitride particles, whereas Al atoms enriched and transformed into TiAl3 phases and formed cBN/AlN, AlB2/TiN, and TiB2/TiAl3-layered structures eventually. The composites maintained good oxidation resistance at 1200 °C. A decrease in the particle size of the TiAl binder improved the uniformity of particle size distribution and increased the flexural strength of the composites.